The impact of Thai multidisciplinary smoking cessation program on clinical outcomes: A multicentre prospective observational study - Chaisai, Chayutthaphong; Thavorn, Kednapa; Wattanasirichaigoon, Somkiat; Rungruanghiranya, Suthat; Thongphiew, Araya; Dilokthornsakul, Piyameth; Lee, Shaun Wen Huey; Chaiyakunapruk, Nathorn (Frontiers in Public Health, 2022)
Introduction Tobacco use is the leading preventable cause of morbidity and mortality worldwide. Since 2010, Thailand has implemented a multidisciplinary smoking cessation clinic, which provides smoking cessation services, but the effectiveness of the clinics was not formally evaluated. This study was conducted to assess the real-world effectiveness of this multidisciplinary smoking cessation program. Methods We conducted a prospective, multicentre, observational study in Thai participants aged 13 years and older in 24 smoking cessation clinics across Thailand's 13 health regions. Each clinic offered smoking cessation interventions according to the well-established 5As model for smoking cessation (Ask, Advise, Assess, Assist, and Arrange). Outcomes of interest were continuous abstinence rates (CAR) at 3, and 6 months. Biochemical confirmation and self-reporting were used to assess the outcomes. Descriptive statistics (mean, SD, median, IQR, and percentage) were used to analyse the smoking cessation outcomes in both intention-to-treat and per-protocol analysis approaches. Results Smokers receiving services from the Thai multidisciplinary smoking cessation clinics had CAR of 17.49% and 8.33%, respectively, at 3 and 6 months. For those with cardiovascular disease (CVD) or cerebrovascular disease, CAR was found to be 26.36% at 3 months, and 13.81% at 6 months. While participants with chronic obstructive pulmonary disease (COPD) had CAR ranging from 32.69% at 3 months to 17.31% at 6 months. Conclusion The multidisciplinary team smoking cessation clinic was effective in assisting smokers in quitting smoking. The effectiveness of the clinic was more pronounced for smokers with CVD, cerebrovascular disease, or COPD. Findings from this study support a decision to include multidisciplinary smoking cessation clinics in the universal health care benefit package.